Prediction of G gene epitopes of viral hemorrhagic septicemia virus and eukaryotic expression of major antigen determinant sequence - Sun, T.; Yin, W-L.; Fang, B-H.; Wang, Q.; Liang, C-Z.; Yue, Z-Q. (Cellular and Molecular Biology, 2017)
This study aims to express fish Viral hemorrhagic septicemia virus (VHSV) G main antigen domain by using Bac-to-bac expression system. Using bioinformatics tools, B cell epitope of VHSV G gene was predicted, and G main antigen domain was optimized. GM gene was inserted into pFastBac1 vector, then transferred recombinant plasmid into DH10Bac to get recombinant rBacmid-GM. Obtained shuttle plasmid rBacmid-GM was transfected into sf9 cells. GM expression was examined using by PCR and western-blot. Results indicated that G main antigen domain gene of VHSV was successfully cloned and sequenced which contains 1209 bp. PCR proved that shuttle plasmid rBacmid-GM was constructed correctly. SDS-PAGE electrophoresis analysis detected a band of protein about 45kD in expression product of G gene. Obtained recombinant G protein reacted with VHSV-positive serum that was substantiated by western-blot analysis. In conclusion, the main antigen domain of VHSV G was successfully expressed in the Bac-to-Bac baculovirus system.